2016
DOI: 10.1016/j.yqres.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of climate change and land use on northern Labrador forest stands based on paleoecological data

Abstract: We reconstructed the late Holocene vegetation of the Nain region (northern Labrador, northeastern Canada) in order to assess the influence of climate and historic land use on past shifts in forest composition. Chronostratigraphy was used in combination with macrofossil and pollen data from monoliths sampled from four peatlands. Paleoecological reconstructions produced a vegetation history spanning 4900 years for the Nain region that is largely concordant with other studies in Labrador. An initial open forest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…At other sites in the northern hemisphere, e.g. the Hudson Bay Lowlands, interior Alaska and in the Sudety Mountains, S. lindbergii macrofossils are found during a wet poor‐fen stage with S. jensseni / balticum , S. magellanicum , S. riparium , S. balticum , S. russowii , Eriophorum angustifolium and P. strictum (Kuhry, ; Jones et al , ; Lemus‐Lauzon et al , ; M. Gałka and B. Fiałkiewicz‐Kozieł, unpubl. data).…”
Section: Discussionmentioning
confidence: 99%
“…At other sites in the northern hemisphere, e.g. the Hudson Bay Lowlands, interior Alaska and in the Sudety Mountains, S. lindbergii macrofossils are found during a wet poor‐fen stage with S. jensseni / balticum , S. magellanicum , S. riparium , S. balticum , S. russowii , Eriophorum angustifolium and P. strictum (Kuhry, ; Jones et al , ; Lemus‐Lauzon et al , ; M. Gałka and B. Fiałkiewicz‐Kozieł, unpubl. data).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple recent studies have demonstrated local human impacts on subarctic forests in Labrador (northeastern Canada) including through the direct harvesting of wood (Roy et al 2012(Roy et al , 2017Lemus-Lauzon et al 2016 and through cultural land and fire management (Lemus-Lauzon et al 2012;Oberndorfer et al 2017;Cuerrier et al 2019). As pointed out by these authors, studies of the ecological history of northern forests and of their management frequently underestimate or ignore the scale of anthropogenic forest impacts in regions with histories of minimal commercial or industrial forestry activity.…”
Section: Introductionmentioning
confidence: 99%
“…The scarcity and short time span of the instrumental record (late 19th century), the considerable regional disparities, and the lack of spatial and temporal resolution of palaeoenvironmental reconstructions near settlement areas do not allow us to document, more precisely, the extent and specificity of environmental change in Labrador, particularly in lake ecosystems, in response to late Holocene climatic fluctuations (particularly Medieval Warm Period (MWP), LIA, and recent warming) and anthropogenic forcings. While palaeoenvironmental and geoarchaeological research has demonstrated that anthropogenic activities (e.g., wood harvesting) contributed to the transformation of the terrestrial landscapes of the Nain Archipelago concomitantly with late Holocene climatic variations, notably from the 17th to late 19th century [5][6][7][35][36][37], their effects on aquatic ecosystems have rarely been studied in the region.…”
Section: Palaeoclmatic Contextmentioning
confidence: 99%